Ultrasound-Assisted Rapid Synthesis of Functionalized 1,2-Teraryls by Ring Transformation Methodology - Krishnan, Manjula; Singh, Fateh V. (Synthesis, 2022)
The function of styryl acetate as a carbanion nucleophile source has been explored in the ring transformation reaction of 2H-pyranones. The ultrasound-assisted carbanion-induced ring transformation of 4-amino-6-aryl-3-cyano-2H-pyran-2-ones using (E)-styryl acetate in the presence of KOH and DMF at room temperature is presented as an alternative strategy for the synthesis of functionalized 1,2-teraryls in high yields. This metal-free methodology provides easy access to a series of 1,2-teraryls and features broad functional group tolerance and mild reaction condition. Single crystal X-ray diffraction analysis of 4-(piperidin-1-yl)-6-(thiophen-2-yl)-[1,1′-biphenyl]-3-carbonitrile indicated that the crystal belongs to monoclinic system with a P21 space group having twisted aryl rings.
Keywords: 1,2-teraryls; ring transformation methodology; 2H-pyranones; ultrasound-assisted synthesis; terphenyls; metal-free reaction; carbanion-induced reaction